Effect of fermented rice bran flour in artificial feed on survival rate and feed conversion ratio of tilapia, Oreochromis niloticus (Linnaeus, 1758) - Surianti Surianti; Hasrianti Hasrianti; Wahyudi Wahyudi; Muh Irwan (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2021)
Tilapia cultivation has the potential to be developed in Indonesia, especially in South Sulawesi. However, the obstacle faced in tilapia cultivation is feed; the price is relatively high because the raw materials are still imported. One of the efforts to overcome dependence on imported feed raw materials is using local raw materials, namely rice bran. This study aims to determine the best type of probiotic in hydrolyzing rice bran flour into artificial feed on survival and conversion ratio of tilapia fish feed. This research was conducted in Sidenreng Rappang Regency. The test animals used were tilapia larvae with an average size of 1.03 g. The maintenance container is a tarpaulin pond with a size of 1 m x 1 m x 1 m filled with 85 L of freshwater. The study was designed using a completely randomized design consisting of four treatments and three replications. The fermenting materials used as treatment were Bacillus sp., Lactobacillus sp., Aspergillus nigers, Yeast (Acetobacter). The test feed was given to 20 tilapia larvae stocked in each container for 60 days of rearing. The survival data and feed conversion ratio for tilapia were analyzed using analysis of variance (ANOVA). The results showed that tilapia fed fermented rice bran feed using the fermenter Lactobacillus sp. had a significant effect on survival (SR) with a value of 85% and the feed conversion ratio (FCR) of tilapia with a value of 2.23. Abstrak Usaha budidaya ikan nila sangat berpotensi untuk dikembangkan di Indonesia khususnya di Sulawesi Selatan. Akan tetapi kendala yang dihadapi dalam budidaya ikan nila yaitu pakan, harganya cukup mahal karena bahan baku masih diimpor. Salah satu upaya mengatasi ketergantungan bahan baku pakan impor adalah pemanfaatan bahan baku lokal yaitu dedak padi. Penelitian ini bertujuan menentukan jenis probiotik yang terbaik dalam menghidrolisis tepung dedak padi ke dalam pakan buatan terhadap sintasan dan nisbah konversi pakan ikan nila. Penelitian ini dilaksanakan di Kabupaten Sidenreng Rappang. Hewan uji yang digunakan adalah larva ikan nila berukuran rata-rata 1,03 ±0,02 g. Wadah pemeliharaan adalah kolam terpal dengan ukuran 1 m x 1 m x 1 m3 yang diisi air tawar sebanyak 85 L. Penelitian didesain dengan menggunakan Rancangan Acak Lengkap yang terdiri atas empat perlakuan dan tiga ulangan. Bahan pemfermentasi yang digunakan sebagai perlakuan yaitu Bacillus sp., Lactobacillus sp., Aspergillus nigers, Ragi (Acetobacter). Pakan uji diberikan pada larva ikan nila yang ditebar sebanyak 20 ekor setiap wadah selama 60 hari pemeliharaan. Data sintasan dan nisbah konversi pakan ikan nila yang diperoleh dianalisis dengan menggunakan analisis ragam (ANOVA). Hasil penelitian menunjukkan bahwa ikan nila yang diberi pakan dengan kandungan dedak padi terfermentasi menggunakan fermentor Lactobacillus sp. memberikan pengaruh yang nyata terhadap sintasan (SR) dengan nilai 85% dan nisbah konversi pakan (NKP) ikan nila dengan nilai 2,23.